NAVIGATING EMPIRES: THE EVOLUTION OF MARITIME TRADE AND REGIONAL POWER DYNAMICS IN MEDIEVAL SOUTH INDIA - Pajisha M; K. S. Soumya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Vijayanagara Empire’s expansion in South India during the 14th and 15th centuries transformed regional maritime trade, extending its influence to overseas territories and integrating into global trade networks. Key rulers such as Harihara II and Devaraya II played pivotal roles in enhancing port facilities and trade routes, notably developing Palavekkad and Thirumenapatto as major trading hubs.The Later Pandyas revived trade relations with China during the Ming Dynasty, navigating the tribute system and facilitating the flow of goods such as pearls and textiles between Tamil Nadu and China.The 15th century saw a shift in trade routes from Tamil Nadu to the Malabar Coast, with ports like Kozhikode and Kochi emerging as prominent trade centres, reflecting changes in global trade dynamics.These developments reshaped regional economies, influenced trade patterns, and highlighted South India’s role in the broader medieval global economy.